Social support, self-efficacy and academic satisfaction of university students during the COVID-19 lockdown - José-Manuel Tomás; Melchor Gutiérrez; Salvador Alberola (Universidad de Navarra, 2022)
This work aimed to analyze the relationships between the students perceived institutional support, teachers' support, peers' support, and their academic satisfaction, mediated by their self-efficacy in information and comunication technologies (ICT). Participants were 157 students who were studying from first to fourth year in different disciplines of the Valencia University. Structural equation models with latent factors were tested. A final model had satisfactory fit indices to the observed data. It is worth highlighting the strong direct effect of the teaching staff support on student' academic satisfaction, with less weight, although significant, being the effect of institutional support. In conclusion, teacher's figure is of paramount importance for student's academic satisfaction.